2020
DOI: 10.1210/clinem/dgaa513
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone and Ovarian Reserve: Update on Assessing Ovarian Function

Abstract: Context Anti-Müllerian hormone is produced by granulosa cells of small growing follicles in the ovary. Serum AMH levels strongly correlate with the number of growing follicles, and therefore it has received increasing attention as a marker for ovarian reserve. This review summarizes recent findings and limitations in the application of serum AMH in ovarian reserve assessment. Evidence acquisition A PubMed search was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
235
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(277 citation statements)
references
References 98 publications
6
235
0
9
Order By: Relevance
“…AL-133 (32/33) detected proAMH, AMH N,C, and AMH C ( Table 1 ). The known proteolytic processing of AMH [i.e., cleavage at amino acid positions 451 and 229 ( 20 , 24 , 26 )] introduces conformational changes, which may change the affinity of different antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AL-133 (32/33) detected proAMH, AMH N,C, and AMH C ( Table 1 ). The known proteolytic processing of AMH [i.e., cleavage at amino acid positions 451 and 229 ( 20 , 24 , 26 )] introduces conformational changes, which may change the affinity of different antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Additional proteolytic cleavage of the AMH N,C complex leads to dissociation of AMH N and AMH C, with the AMH C remaining biologically active and inducing intracellular SMAD signalling upon receptor binding ( Figure 1 ) ( 23 ). ProAMH has two known cleavage sites: at amino acid (aa) 451 (between the AMH N and AMH C domains) and at aa 229 in the AMH N region, giving rise to additional cleavage products ( 21 , 24 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted by Hiadzi et al, 2019 [2] showed that, many sub-fertile couples start seeking fertility treatment from herbal products and associated traditional services, then through religious leaders and by the time they visit ART centres, the woman will eventually be advanced in age. Epidemiological data have consistently shown that fertility declines as early as the middle of the third decade [3] and female age remains the most important determinant of success [4] in an IVF programme. Though there is no strict definition of advanced reproductive age in women, subfertility becomes more pronounced after the age of 35 years [5] (Practice committee of ASRM, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…When follicles grow to over 8 mm during the FSH-dependent stage, AMH expression rapidly declines until it is absent [ 2 ]. Serum AMH levels are strongly and positively associated with the number of growing follicles and can serve as a serum marker for functional ovarian reserve [ 3 ]. However, serum AMH levels negatively correlate with age in adult women.…”
Section: Introductionmentioning
confidence: 99%